Producing accountability with autonomy in Denmark and England: the analytical potential of assemblage theory with critical realism in comparative education - Alison L. Milner; Christian Ydesen (Taylor & Francis Group, 2024)
School autonomy with accountability (SAWA) reforms have developed in diverse forms in Northern Europe. Following processes of decentralization to the municipal and school levels, quality assurance and inspection became key to the test-based accountability agendas of Denmark and England respectively. With an abductive approach, we explore the epistemological potential of a hybrid theoretical framework, which combines assemblage theory with critical realism, to analyze the production stories of these two policy instruments. Drawing on data from an international comparative research project, and more recent policy document analyses, we examine the arrangement of social entities - discourses, instruments, technologies, artefacts, and actors - that led to particular accountability outcomes within these specific educational assemblages. We argue that, despite distinctions in their social entities, the dominant state assemblages of accountability in Denmark and England have been captured by the global SAWA and capitalist assemblages at distinct times. Although school actors are incorporated into, and antagonistic towards, the state assemblages, change is limited due to the resilience of the underlying logic of epistemic governance and the desire to improve educational standards for a global knowledge economy. We conclude briefly with an assessment of the utility of the hybrid framework to the comparison of SAWA.